The use of geotextiles for soil erosion control - Rickson, R. Jane (Cranfield University, 2000)
Geotextiles are used by engineers for a variety of applications, such as filtration, separation, slope stabilisation, drainage and soil erosion control. At present, there is little research on geotextiles for erosion control, despite the increase in their use in the field. There are no guidelines for soil conservationists or field/civil engineers to indicate which product will be most effective for any given site. Studies that do exist tend to be qualitative and descriptive, rather than quantitative and scientific. There is also very limited identification and understanding of the salient physical properties of erosion control geotextiles. The present laboratory experiments aim to contribute objective, scientific data. These experiments evaluate the performance of seven different erosion control geotextiles. The products are selected to be representative of the types of erosion control geotextile currently on the market. The products tested are four natural fibred products, including three woven bionets and one biomat. Three synthetic geomats are also tested: two are buried and one is installed on the soil surface. A bare soil plot is used as the control in all the tests. The experiments are designed to simulate erosion processes at the sub-process level. This is achieved by simulating rainsplash and overland flow, both separately, and in combination. Experimental variables used include rainfall intensity (35 mm/hr, 95 mm/hr and 115 mm/hr), overland flow rate (40 ml/sec) and soil type (sandy loam and clay loam). Runoff volume, infiltration volume and soil loss are collected for each experimental run. From the results of these tests, it is possible to indicate how geotextiles modify incoming rainfall and surface hydrology, and therefore affect rates of soil detachment and transport. The results show that erosion control effectiveness is influenced by the physical characteristics of the geotextiles tested, soil type and rainfall intensity. The products tested have insignificant effect on runoff volumes generated, but soil loss varies considerably for the different treatments. Overall, the natural, woven products Rickson, R.J. 2000 Cranfield UNIVERSITY perform most effectively, reducing soil loss significantly when compared with the bare soil control, for all experimental conditions tested. The buried, synthetic products were not as efficient at controlling soil loss: under some experimental conditions soil loss from these treatments was even greater than that observed for the bare soil control. The results are analysed in terms of the salient properties of the geotextiles, which explain their performance. The salient properties identified were: percentage ground cover provided by the geotextile, water holding capacity, Geotextile Induced Roughness, wet weight of geotextile and ability to increase overland flow depth. The limitations of the laboratory-based research are indicated, such as the problems of extrapolation from small test plots up to field scale applications, and the difficulties of controlling the interactions between the geotextiles and the experimental variables. Implications of the research to the erosion control industry are made. For existing and potential end-users of erosion control geotextiles, the decision to specify these products is not only related to technical performance (as quantified in the laboratory studies), but also to the assessment of erosion risk, costs and compliance criteria. For manufacturers, identification of the salient properties of effective erosion control geotextiles helps in the development and design of improved products. Recommendations for future research include study of the variability in geotextile performance as related to external factors such as soil type, rainfall intensity, slope steepness and slope length. Incorporating the effect of erosion control geotextiles into physically based erosion prediction models such as EUROSEM and WEPP has great potential. Identification and quantification of critical values of the salient properties of erosion control geotextiles has considerable scope. The performance of geotextiles at controlling erosion over longer time periods (greater than one storm event) requires further investigation. Finally, research into the synergistic relationships between geotextiles and vegetation also warrants further research.